Experimental investigation on the steel standing seam roof systems subjected to wind uplift - Reddy, S. Ravikanth; Jayachandran, S. Arul (Journal of Structural Engineering, 2024)
Standing Seam Metal Roofing (SSMR) systems have advantages of weather tightness, leak-proof performance, durability, and cost-effectiveness. Codification of SSMR designs is quite complex due to the interaction of several components. The design of supporting purlin is also difficult when the resistance from sheeting is accounted for. Since numerical models have limitations to capture this interaction, experiment based empirical equations are the only way to design these systems. Two types of profiles namely Flexlok® and Tracdek® profiles are widely used in practice. In the former, the roof sheets under upward wind depend on the clamping force between the sheet profile and a clamping device called a halter. The latter gets its strength from the integral folding of the sheet with the mechanical clamping device. Although these two systems have different load carrying mechanisms, the behavior of both has an impact on the secondary load carrying systems such as purlins. Unless this interaction of the sheeting and the secondary frame systems are experimentally evaluated, the design does not become rigorous. This paper presents experimental studies on the interaction behavior of two types of SSMR systems subjected to wind uplift. A special vacuum chamber is fabricated as per specifications in ASTM E1592 - 05(2017) for creating air-pressure differences. The various modes of failure in these two types of roof systems are captured in the experiments which will influence the overall behavior of the roof systems. The halter panel disengagement failure mode observed in Flexlok® panels and Tracdek® system undergo failure by the fracturing of sheets. During the interaction, the Flexlok® system experiences component failure, and hence its effect on the secondary frame is not significant. However, the Tracdek® system has a big influence on the interaction due to the larger restraints provided by the integral folding of clips with sheeting. The present design methods currently used to design the SSMR systems, underestimate the interaction effect in the Tracdek® system in which there will be a combined failure of purlins and the roofing sheets. However, purlins supporting flexlok system won’t fail since the sheet disengages early. The present experiments bring out the various failure modes and their failure load which are very essential for the codification of SSMR designs.